Practical model-based systems engineering - Fernández Pérez, José Luis; Hernandez, Carlos (Artech House, 2019)
For systems engineers and practitioners, this book provides the analytic, design and modeling tools of the Model Based Systems Engineering (MBSE) methodology of Integrated Systems Engineering (ISE) and Pipelines of Processes in Object Oriented Architectures (PPOOA) methodology. -- Edited summary from book.
Keywords: Engineering mathematics.; System design.; Systems engineering -- Mathematical models.; elektronické knihy; electronic books